Pengaruh Pemekaran Kecamatan Terhadap Persepsi Masyarakat Tentang Pelayanan Publik dan Kesejahteraan Masyarakat : Studi di Kecamatan Ngusikan Kabupaten Jombang Jawa Timur - Hidayani, Nurul; , Drs. Muhammad Musiyam, MTP (2016)
District of Ngusikan a new sub-district, which is a division of the District Kudu based Jombang District Regulation No. 15 of 2000. The purpose of this study were: 1) to analyze the effect of splitting districts on public perception of public services and social welfare; 2) to analyze the effect of splitting districts against public perceptions of rural development. The method used is descriptive analysis. The population in this research that the villagers and village Mojodanu Ngampel as rural sample of 91 respondents with data collection techniques used are observation, documentation, and questionnaire. The results showed that 86.6% of respondents said the level of public services after the separation increases and decreases of 13.4% of respondents stated. 78% of respondents stated that the level of social welfare after separation increased, while 22% of respondents stated decrease. Ngampel village with a number of respondents 39 people, 71.8% of them declared rural development increased after the enlargement, and 28.2% said declines. Mojodanu village with a number of respondents 52 people, 86.5% of them declared rural development increased after splitting districts and 13.5% of respondents stated decrease.